Zero-hours contracts: Flexibility or insecurity? Experimental evidence from a low income population - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2020)
This paper experimentally studies labour supply responses to earnings uncertainty. 301 low-income, working age, non-student individuals took part in an on-line experiment simulating standard and zero-hours contractual conditions. Results unambiguously support the hypothesis that work uncertainty discourages work. This is not only because variability in work availability reduced total expected pay but also because uncertainty itself is perceived as detrimental. Uncertainty is avoided even at the cost of lower total earnings. Interactions between work related uncertainty and the benefit system are important. Both the use of benefits as insurance when work is unavailable and benefit sanctions can increase incentives to take up insecure work.
Keywords: D8; I38; J83; J88; 330; precarious work; economic insecurity; wages; labour supply; low income; experiment